Peningkatan Hasil Belajar Siswa Menggunakan Model Two Stay Two Stray dalam Pembelajaran IPS di Kelas V - Hasibuan, Sulastri Qomariah; Arwin, Arwin; Eliyasni, Rifda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this study was to describe and increase in student learning outcomes in social studies learning by using the Two Stay Two Stray model in the fifth grade of elementary school. Types of this research was classroom action research with qualitative and quantitative approach. The research subject was 34 grade V students consisting of 18 men and 16 woman. The research procedure consistend of planning, implementing, observing, and reflecting. The result of the study showed and increase in aspects: a) RPP cycle I with an average of 71,42% and cycle II 92,85%, b) implementation on the aspect of the teacher cycle I with an average of 76,78% and the second cycle 96,42%, while for the implemenetation of aspect of the students of the first cycle with an average 74,99% and cycle II 92,85%, c) learning outcomes in the first cycle with an average of 73,00 and cycle II 86,19. The conclusions from the result of the research conducted are using the Two Stay Two Stray model can improve student learning outcomes in social stundent learning in class V SDN 05 Air Tawar Barat City of Padang.  Keywords : Learning outcomes, Social science, Two Stay Two Stray